Role of Corneal Collagen Cross Linking in Halting the Progression of Keratoconus: A Contralateral Eye Study - Taiba Baig, Tahira Afzal Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the efficacy of Corneal Collagen Cross-Linking in preventing the progression of Keratoconus by comparing changes in Maximum Simulated Keratometry (K-max) in treated and untreated eye of the same patient. Methodology: All the cases, that met the inclusion/exclusion criteria (with complete pre-operative examinations), were enrolled in the study. Patients gave informed permission. In each patient, a computerized random number table was used to pick one eye for treatment and the other as a control. Patients were told to stop wearing hard contact lenses 3 weeks before the treatment and soft lenses 1 week before. After pre-op assessment, the selected eye underwent CXL. To control bias, only one experienced surgeon carried out the procedure and a thorough examination was done at 1st post-op day, 01 week, 01, 03 and 4 months after CXL. Main outcome measure during follow up was K-max as measured by Corneal Topography using Galilei G4. One experienced person performed corneal topography for all eyes to control bias. Results: In our study, mean age was 20.55+6.27 years, 60.61%(n=20) were male while 39.39%(n=13) were females. Comparison of the efficacy of corneal collagen cross-linking in preventing the progression of keratoconus by comparing changes in maximum simulated keratometry (K-max) in treated and untreated eyes of the same patient shows that 96.97%(n=32) in CXL and 3.03%(n=1) in control group showed efficacy whereas remaining 3.03%(n=1) in CXL and 96.97%(n=32) in control group had no efficacy, p value was 0.000. Conclusion: We concluded that Corneal Collagen Cross Linking is significantly effective in preventing increase in K-max when compared with the control group. Keywords: Keratoconus, Maximum Simulated Keratometry, Corneal Collagen Cross-Linking, Efficacy